The Meaning of Slogan in Cosmetics Advertisement: Semantics Study - Asila Gustavia Kurman; Ida Zuraida (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Advertising is one of the most influential media for selling a product, especially in this digital era. Advertising has a huge impact on a company or individual to market their products. When opening social media, there are so many ads that appear, and it is the quirky ads that can attract the attention of people who see it. One of the interesting advertisements is that there is a slogan that makes readers curious about the product. The most of the sentences in the slogan are difficult for readers to understand which makes readers curious and want to find out more about the product. This study used a qualitative method where the process and meaning are more highlighted in this study. The theoretical basis is used as a guide so that the research focus is in accordance with the facts. The main theory used in this paper is the Seven Types of Meaning by Leech (1981). The result of this study finds that five data in this paper, all of them contain associative meanings, three of them are affective meanings and two of them are connotative meanings.